Analysis of Students' Cognitive and Affective Ability in the FliCKu Learning Model Based on Bloom's Taxonomy - Nanda Fatma Nuraini; Tantri Mayasari; Farida Huriawati; Mislan Sasono (UNIVERISTAS PGRI MADIUN, 2022)
Entering the New Normal era, educators think hard about how new steps or new methods should be taken in learning activities. The teacher hopes that in this new normal era, student learning achievement can increase and there is synchronization during online and offline learning. In order to meet the teacher's expectations, the researcher offers the Flipped Classroom learning model combined with the Kumon learning model, which in this study is called FliCKu. The aims of this study are (1). To find out the FliCKu learning model can improve students' abilities in the cognitive and affective aspects of students. (2). To determine the increase in students' cognitive abilities based on Bloom's taxonomy. The research method used is the mix method with a sample of 22 students. The result of this study is that the FliCku learning model can improve students' cognitive and affective aspects. From the results of the analysis of increasing students' cognitive abilities based on Bloom's taxonomy, at the cognitive level C1 shows students are in the very high category. At the cognitive level C2 shows students are in the very high category. At the C3 cognitive level, it shows that students are in the high category. At the C4 cognitive level, it shows that students are in the medium category. At the cognitive level of C5, it shows that students are in the low category.